CORRELATION WITH SERUM MELATONIN LEVELS TO THE PREVALENCE OF TYPE II DIABETES MELLITUS IN BORN BLIND SUBJECTS - PROF.DR.N.N.ANAND,; PROF.DR.V.PADMA, (International Journal of Pharma and Bio Sciences, 2015)
Born Blind subjects are able to lead a near normal life with a little percentage of chronic ailments like Diabetes Mellitus, Hypertension, Renal disease and Cardio Vascular problems. To detect the prevalence of T2DM in Born Blind subjects and to find out the prevalence of metabolic syndrome .To find out the levels of melatonin in born blind subjects . 500 born blind subjects were recruited in and around Chennai. Participants were within 30-60 years. Both sexes are included. Among 500participants , 404 males and 96 females. 210(42)blind people had abnormal waist hip ratio. A high level of Serum Melatonin level was observed among them at 38.5±0.6. The Prevalence of Prediabetes was 11(2.2) , hypertension to be among 19(3.8) and a negligible case of 1(0.2) with both conditions. Average HbA1C was 5.9. Higher melatonin secretion was associated with a lower risk of developing T2DM.